Situational Analysis of Eye Care Services in South Sulawesi - Ahmad Ashraf Amalius (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2016)
Background: VISION 2020 as the global initiative program almost reaches the time limit. Every country in all over the world ran their programs in eye care services based on the strategic components of VISION 2020 including in Indonesia since the government declared it in 1999. The aim of this study is to report whether the condition in South Sulawesi as one of the province in east Indonesia sufficient to meet VISION 2020 target.Methods: This is a descriptive study with the qualitative and quantitative approach. Data were collected by interviewing and distributing semi-structured questionnaire to all stakeholders involved in eye care services in South Sulawesi, including ophthalmologists, ophthalmic nurses, Indonesian Ophthalmologists Association committee, provincial and district health office staffs.Results: South Sulawesi has population of 8,324,000, consists of 24 districts/city, 33 hospitals and 440primary health care (Puskesmas). Human resource data showed 67 ophthalmologists including subspecialists, 17 trained ophthalmic nurses, 6 refractionists, 3 optometrists, 1 orthoptist, and 3 counselours. Total number of cataract surgery in 2015 are 15,075 eyes. Complete data for refractive error screening and examination, glaucoma, diabetic retinopathy and corneal diseases are not available. Some advocacies and workshops had been held. Supported from government and NGO took role in building capacity for the services.Conclusion:According to VISION 2020 program, eye care services in our province is not yet ideal; but the process to build capacity, especially for 5 main focus eye disease, is still on the track.Â Keywords: VISION 2020, eye care services, cataract surgery, human resource, advocacy